Chemopreventive effects of fermented brown rice and rice bran against 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone-induced lung tumorigenesis in female A/J mice - Phutthaphadoong S. (2014)
The most common cause of human lung cancer is suggested to be exposure to the carcinogens in tobacco smoke. Among the multiple chemicals in tobacco smoke, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) has been regarded as one of the important agents for generation of lung cancers. Previously, our studies proved that fermented brown rice and rice bran (FBRA) has chemopreventive effects against carcinogenesis of the colon, liver, stomach, bladder and esophagus. In the present study, we examined possible chemopreventive effects of FBRA on the NNK-induced lung tumorigenesis in mice. Six-week-old female A/J mice were divided into 8 groups, and groups 1-5 were given NNK (10 mmol) by i.p. injection at week 7. Groups 2 and 3 were fed with diet containing 5 and 10% FBRA during the initiation phase, respectively. Groups 4 and 5 were fed with 5% and 10% FBRA during the post-initiation phase. Groups 1 and 6 were given control diet throughout the experiment. Groups 7 and 8 were given the diet containing 5 and 10% FBRA throughout the experiment, respectively. In both initiation (group 3) and post-initiation phase (group 5), 10% FBRA exposure significantly reduced the multiplicity of lung tumor (group 3, 2.35±2.13; group 5, 3.00±1.52; group 1, 4.08±1.85; p<0.006 and 0.04, respectively). Furthermore, administration of FBRA during the post-initiation phase significantly decreased the tumor size in comparison with that of control mice (0.66±0.32 vs. 0.77±0.33 mm). Treatment of 10% FBRA significantly reduced the mRNA expression levels of cytochrome P450 2A5 (Cyp2a5), which is known to be closely related to the human CYP2A6 enzyme that is involved in the mutagenic activation of NNK, in the lung but not liver tissues. A significantly reduced index of Ki67 positivity of lung tumors in group 5 was confirmed when compared with tumors of the control group (0.065±0.016 vs. 0.114±0.025). These findings suggest that FBRA has inhibitory effects on NNK-induced pulmonary tumorigenesis in A/J mice in both during initiation and post-initiation treatment, which is possibly associated with the induction of Cyp2a5 in the lung and the reduced proliferation rate of tumor cells. FBRA may be a promising chemopreventive agent for human lung cancers.